A novel bedside rule-in test for tuberculous meningitis in human immunodeficiency virus-infected adults - Broger, Tobias; Nicol, Mark P. (Clinical infectious diseases, 2021)
(See the Major Article by Quinn et al on pages e3428-34.)Tuberculous meningitis (TBM) likely affects >100 000 people per year [1]. While this represents approximately 1% of all tuberculosis (TB) cases, TBM is disproportionately important because it kills or severely disables half of those affected [2]. Major risk factors for TBM are young age [3] and human immunodeficiency virus (HIV) infection.Diagnosis of TBM is a challenge because clinical features are nonspecific, laboratory tests are insensitive, and mycobacterial culture is too slow to have meaningful clinical impact. Treatment delay is the strongest risk factor for death [2]; sensitive diagnostics with short turnaround times are urgently needed. Rapid nucleic acid amplification tests, such as Xpert MTB/RIF Ultra (Ultra), have shown good sensitivity (77%) against culture-confirmed TBM [4], but require large cerebrospinal fluid (CSF) volumes [5] and are not yet widely available, particularly close to the point of care in many high-burden countries [6].